Student Assistance in Addressing Educational Needs: A Strategy of Quality Education Project of Universidad Nacional, Costa Rica - Fontana Hernández, Angélica (2013)
The Quality Education Project of the Universidad Nacional, Costa Rica (UNA Educación de Calidad) was created in 1998 as a direct response channel for students with disabilities or educational needs in their professional training. Considering the experience generated throughout the project’s activity at the University in 2008 and 2010, the project team decided to evaluate the work that had been developed with the assistance of a group of students, in order to identify the results of services provided and make the appropriate changes. This process was implemented through workshops, which enabled the group to observe the performance of each participant, individually and collectively, at different times. During the workshops, group work guides were used in the discussion sessions on educational needs and assistance methods, an instrument with incomplete phrases was applied, a video on the issue being discussed was shown, and a final analysis was made on the feelings and emotions that emerged from the assistance activities. Among the main findings, this study points out a range of assistance methods developed by each student to respond to the educational needs of his/her peers, based on the personal and social conditions of each one of them; in addition to a number of spaces created for exchange and interaction. This helped both groups of students to work in the reconstruction of the traditional concept that is associated to the term of “disability” and further develop personal abilities and skills that will contribute to the students’ permanence in the university, as well as to their social and labor inclusion. The study provides useful recommendations to meet the needs of the student population participating in the Project, particularly in terms of follow-up and assistance methods, a challenge to be undertaken in the everyday activity of UNA Educación de Calidad.